ASSESSMENT OF THE EFFICIENCY OF CALCIUM ACETATE MONOHYDRATE-GLYCEROL-METHANOL CATALYST (CATALYST X) FOR POLYGLYCEROL SYNTHESIS - Mulki Anas Suyadi, Malikul
As the world's largest biodiesel producer, Indonesia needs more efficient and higher-quality methods to valorize biodiesel industry by-products, one of which is the production of polyglycerol from purified crude glycerol. Industrial-scale polyglycerol production has not yet been established in Indonesia, so research on efficient and sustainable polyglycerol production is necessary for future industrial-scale application. Industrial-scale polyglycerol production typically uses KOH and Na(OH)2 catalysts at relatively high reaction temperatures, resulting in low glycerol conversion and yield. To ensure that future polyglycerol industries in Indonesia can compete with those abroad, research on economical raw materials and production processes is required. This study evaluates the catalytic activity of Catalyst X, a new catalyst synthesized from calcium acetate monohydrate, glycerol, and methanol for polyglycerol synthesis from glycerol. FTIR characterization of Catalyst X indicates the presence of C-O, C-H, and C-C bonds. However, XRD analysis reveals that Catalyst X is not identical to calcium diglyceroxide, which was one of the initial research goals. Catalyst X achieved a maximum glycerol conversion of 38.32% with a catalyst-to-glycerol ratio of 1:25 and a reaction time of 8 hours. The selectivity for PG2, PG3, and PG4+ was 27.47%, 6.87%, and 1.07%, respectively. Extending the reaction time to 26.5 hours resulted in higher glycerol conversion but did not align with the initial research objectives. Compared to the use of KOH/DMSO, Catalyst X required higher temperatures and longer reaction times. However, Catalyst X produced polyglycerol that was neither black nor odorous, which is an advantage over KOH/DMSO.